2015
DOI: 10.1308/003588414x14055925060154
|View full text |Cite
|
Sign up to set email alerts
|

Delay in diagnosis and lessons learnt from a case of abdominal wall abscess caused by fishbone perforation

Abstract: Complications following foreign body (FB) ingestion are an uncommon clinical problem. A 59-year-old man presented with a 4-week history of left iliac fossa pain and 1 episode of dark red blood mixed with stools. Inflammatory markers were elevated, and computed tomography (CT) of the abdomen and pelvis showed an ill defined abdominal wall inflammatory collection in close contact with the small bowel loops. He was treated with antibiotics, and follow-up CT, colonoscopy and small bowel enema were mostly unremarka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…It requires a high degree of suspicion as the patient is unable to provide an appropriate history. In a case report by Hakeem et al, there was a 10-month delay in diagnosis of a fish bone perforation of the small bowel with a localized fluid collection 1,2. Only in 1% cases does the foreign body cause complications such as obstruction and perforation.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…It requires a high degree of suspicion as the patient is unable to provide an appropriate history. In a case report by Hakeem et al, there was a 10-month delay in diagnosis of a fish bone perforation of the small bowel with a localized fluid collection 1,2. Only in 1% cases does the foreign body cause complications such as obstruction and perforation.…”
Section: Case Reportmentioning
confidence: 99%
“…In a case report by Hakeem et al, there was a 10-month delay in diagnosis of a fish bone perforation of the small bowel with a localized fluid collection. 1 , 2 Only in 1% cases does the foreign body cause complications such as obstruction and perforation. Dangoisse and Laterre have reported a case of an impacted fish bone in the left lobe of the liver after it perforated the stomach.…”
Section: Case Reportmentioning
confidence: 99%
“…13). Due to the gradual migration of fish bone, the perforated bowel is allowed time to seal off without discernible abnormality on CT [15]. Wu et al reported a case of omental abscess resulting from a fish bone that had perforated the terminal ileum; a fibrotic fistula extended from the site of perforation to the abscess, which was surgically resected [16].…”
Section: Omentummentioning
confidence: 99%
“…Wu et al reported a case of omental abscess resulting from a fish bone that had perforated the terminal ileum; a fibrotic fistula extended from the site of perforation to the abscess, which was surgically resected [16]. Further superficial migration of the fish bone to form an abdominal wall abscess has been reported, and depending on the depth of involvement, may be treated with incision and drainage or laparoscopic surgery [15,17].…”
Section: Omentummentioning
confidence: 99%
“…The risk of intestinal perforation is low and significantly less to be occurred in the large intestine [ 6 ]. If perforation develops, the patient can present either immediately with acute abdomen or later with intra-abdominal collections [ 7 ].…”
Section: Introductionmentioning
confidence: 99%